The philosophy and life of Abu Nasr al-Farabi: knowledge and vision (Journal of Oriental Studies, 2020)
Al-Farabi recieved his initial education in his native village of Visich and continued it in the city of Otrar (Farab). While at the age of forty, in search of knowledge, he moved from the city of Marv, across the Iranian country to the city of Bagdad, where he learned from great teachers of various fields of knowledge, and, as an encyclopedist he formed the basis of his philosophy of Muslim scholar. In this article, based on written sources and scientific conclusions of scientists in al-Farabi studies, we tried to determine through systematic knowledge that the scientist’s philosophy was largely based on the science of logic. At the same time, we tried to find out that his philosophy was based on the principles of Islam and logic of Aristotle. In this regard, we have included the оpinion of scientists in al-Farabi studies, who claim that his treatise «City of dreams» or «Good city» takes beginning from the treatise «Main nodes of thought». We have also developed a new translation version into Persian and Kazakh languages, comparing it with the authenticity of the Arabic version of the treatise «Main nodes of thought» ( ). Since it is very important for Oriental studies to delivery an authentic source in the Kazakh language and thereby creating conditions for independent analysis of our history and culture, avoiding this sphere from the influence of other languages. Key words: Abu Nasir al-Farabi, Islamic philosophy, religion and philosophy, Amin Ahmet Razi, Aristotle, Plato, Abay, theoretical mind, practical mind.